ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN METODE MATERIAL REQUIREMENT PERIOD PADA PERUSAHAAN BATIK CV CEMPAKA DI SURAKARTA - Bagus Wicaksono; Yohanes Djoko Suseno; Erni Widajanti (Universitas Slamet Riyadi, 2020)
This research is an observation. This type of data uses qualitative data and quantitative data. The data source uses primary data and secondary data. Data collection techniques using study documentation. Data analysis uses descriptive method. The results showed that the application of the Material Requirement Planning method could play a role in optimizing the control of raw material inventories at the Batik Company CV Cempaka, this was indicated by the total cost of raw material inventory using the economic order quantity (EOQ) technique of Rp 5,027,000, the total inventory cost raw materials use the period order quantity (POQ) method of Rp. 18,980,800, the total cost of raw material inventories using lot for lot (LFL) is Rp. 17,500,000, and the total cost of inventory for the company's method raw materials is Rp. 27,571,000. From this comparison it can be seen that both MRP techniques namely economic order quantity (EOQ) with a total inventory cost of Rp 5,027,000 is the most optimal in order to achieve optimal optimization of the total cost of raw material inventory because it can save raw material inventory costs by 70%, so the hypothesis 2 which states that: